Design and Build a 2D Mobile-Based Adventure Game Named “Astronaut Go” - Kaleksanan Dwi Ranjis; Cindy Taurusta (Universitas Muhammadiyah Sidoarjo, 2022)
The prolonged Work From Home (WFH) policy causes boredom, saturation and stress to arise so that it can interfere with one's psychology. Therefore, one has to do a lot of activities that aim to entertain oneself so as not to get bored and relieve excessive stress, one of which is by playing online games. Online game is a game that can be accessed by several players who are connected to one internet network. One of the most popular games among the public to entertain themselves is an adventure genre game. Adventure games are one of the most popular genres among the public because the gameplay of adventure games has its own charm and can be used as a learning medium. Indirectly an adventure genre game educates players/users with the aim of learning. Education can be defined as a learning process that aims at developing self-potential to realize a better learning process. In the learning process, one must increase interest in learning, one of which is by making learning methods more interesting and not boring. Then made a 2D adventure game called